Answer:
[tex]F_g=G\times \dfrac{M^2}{d^2}[/tex]
Explanation:
The force of gravity between two bodies is expressed by Newton's law of universal gravitation. The force of atraction is proportional to the product of the masses and inverse to the square of the distance that separates their centers.
[tex]F_g=G\times \dfrac{m_1\cdot m_2}{d^2}[/tex]
Where:
[tex]F_g\text{ is the force of gravity}\\\\m_1\text{ is the mass of one body}\\\\m_2\text{ is the mass of the other body}\\\\G{\text{ is the gravitational constant, }6.67\times 10^{-11}N\cdot m^2/kg^2[/tex]
Replacing the data:
[tex]F_g=G\times \dfrac{(2M)\cdot (2M)}{(2d)^2}\\\\\\F_g=G\times \dfrac{4M^2}{4d^2}\\ \\ \\ F_g=G\times \dfrac{M^2}{d^2}[/tex]